Cone-beam CT-based inter-fraction localization errors for tumors in the pelvic region. (February 2018) - Garibaldi, Cristina; Fodor, Cristiana; Riva, Giulia; Rojas, Damaris Patricia; Dicuonzo, Samantha; Pace, Elisa; Fanetti, Giuseppe; De Marco, Paolo; Dell'acqua, Veronica; Marvaso, Giulia; Leonardi, Maria Cristina; Lazzari, Roberta; et al.
Highlights: Inter-fraction localization errors for 928 patients with pelvic tumors were evaluated with CBCT. Online daily and weekly IGRT protocols were used. Appropriate CTV-to-PTV margins in non IGRT scenario have been proposed. Without IGRT, large CTV-to-PTV margins up to 15 mm are required to account for inter-fraction tumor localization errors. Abstract: Purpose: To evaluate inter-fraction tumor localization errors (TE) in the RapidArc® treatment of pelvic cancers based on CBCT. Appropriate CTV-to PTV margins in a non-IGRT scenario have been proposed. Methods: Data of 928 patients with prostate, gynecological, and rectum/anal canal cancers were retrospectively analyzed to determine systematic and random localization errors. Two protocols were used: daily online IGRT (d-IGRT) and weekly IGRT. The latter consisted in acquiring a CBCT for the first 3 fractions and subsequently once a week. TE for patients who underwent d-IGRT protocol were calculated using either all CBCTs or the first 3. Results: The systematic (and random) TE in the AP, LL, and SI direction were: for prostate bed 2.7(3.2), 2.3(2.8) and 1.9(2.2) mm; for prostate 4.2(3.1), 2.9(2.8) and 2.3(2.2) mm; for gynecological 3.0(3.6), 2.4(2.7) and 2.3(2.5) mm; for rectum 2.8(2.8), 2.4(2.8) and 2.3(2.5) mm; for anal canal 3.1(3.3), 2.1(2.5) and 2.2(2.7) mm. CTV-to-PTV margins determined from all CBCTs were 14 mm in the AP, 10 mm in the LL and 9–9.5 mm in the SI directions for the prostate and the gynecological groups and 9.5–10.5 mm in AP, 9 mm in LL and 8–10 mm in the SI direction for the prostate bed and the rectum/anal canal groups. If assessed on the basis of the first 3 CBCTs, the calculated CTV-to-PTV margins were slightly larger. Conclusions: without IGRT, large CTV-to-PTV margins up to 15 mm are required to account for inter-fraction tumor localization errors. Daily IGRT should be used for all hypo-fractionated treatments to reduce margins and avoid increased toxicity to critical organs.